Investigating hydroclimate changes in Antarctica during 1900-2014 - Silva, Natália (2022)
The hydroclimate of high southern latitudes impacts the Antarctic Ice Sheet (AIS) and, by con- sequence, the global climate. Precipitation (PPT) is directly related to the surface mass balance in the AIS and has increased over the past centuries as a response to global warming. In partic- ular, the upward PPT trend accelerated in the late 20th Century, when anthropogenic forcing overcame natural variability in determining the climate. Using twenty-three CMIP6 models and seven reanalyses, we found PPT changes considering the periods before (1900-1979) and after (1980-2014) the year 1980. In the averaged Austral region, PPT trends for the multi-reanalyses mean grew 60% from the previous period to the contemporary: from 8.2e-3 to 1.3e-2 mm day-1 decade-1 for 1900-1979 and 1980-2014, respectively; The multi-model mean captured a sevenfold acceleration in PPT trends from the before 1980 to the after 1980 period (2.1e-3 to 1.5e-2 mm day-1 decade-1). However, PPT changes were spatially heterogeneous. While a general rainfall increase occurred south of 60° S, the western-West AIS and the Ross Sea regions became drier. We also analyzed the Southern Oceans sea surface temperature and atmospheric circulation, two principal modulators of Antarctic rainfall. Consistent with previous studies, we found that PPT in Antarctica throughout 1900-2014 was primarily determined by atmospheric dynamics rather than the thermodynamical influence of the ocean surface.